A Comparison of Restaurant-Based and E-Commerce Food Delivery: Customer Evaluation Based on Expectations and Satisfaction - Yasirandi, Rahmat; Thanasopon, Bundit (My University, 2024)
This study examines the impact of the COVID-19 pandemic on consumer preferences between restaurant-based and e-commerce food delivery services. Utilizing the E-Service Quality (E-ServQual) model, which includes dimensions such as Efficiency, Fulfillment, Reliability, Privacy, Responsiveness, Compensation, and Contact, the research assesses which delivery method satisfactions align more closely with user expectations through customer evaluations. Methods include a comparative analysis using data collected from surveys. To obtain a robust dataset, the study surveyed 200 consumers who have used both restaurant-based and e-commerce services during the pandemic. This sample size provides sufficient statistical power to discern significant differences between the two service types. Findings indicate that e-commerce platforms generally excel in efficiency, responsiveness, and compensation, whereas restaurant-based services perform better in terms of fulfillment, reliability, privacy, and contact. The results also identify key dimensions from both types of online food delivery services. This analysis provides valuable insights into specific areas where service providers can focus their improvement efforts to meet and exceed consumer expectations. The study contributes to the understanding of shifting consumer behaviors in response to global disruptions like the pandemic.
Keywords: Customer Expectation; Customer Satisfaction; E-Commerce; E-ServQual; Restaurant-based